1996
DOI: 10.2166/wst.1996.0348
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds (VOC) at some sewage treatment plants in Poland

Abstract: Volatile organic compounds have been measured at two relatively large sewage treatment plants. Quantitative estimation of benzene, toluene, m.p-xylene, o-xylene and isopropylbenzene have been made for raw sewage, sewage after primary treatment and after biological treatment. Also measurements of 14 different volatile organic compounds in the ambient air, close to screens, and the air above (0.5 m above) aeration tanks have been done. Tests on air stripping of added volatile organic compounds to clean water hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Toluene is a compound that often occurs in municipal and industrial effluents in the range from at detectable levels to ~86 μg/L ( Bell et al, 1988 ; Namkung and Rittman, 1987 ) and higher to ~115 μg/L, for example in raw wastewater at a treatment plant in Skoczow, Poland ( Suschka et al, 1996 ). Toluene, like other volatile organic compounds (VOCs), which include benzene, ethyl benzene, and xylene, in the process of biological treatment are partly biodegraded, or stripped to the atmosphere during aeration ( Zu et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toluene is a compound that often occurs in municipal and industrial effluents in the range from at detectable levels to ~86 μg/L ( Bell et al, 1988 ; Namkung and Rittman, 1987 ) and higher to ~115 μg/L, for example in raw wastewater at a treatment plant in Skoczow, Poland ( Suschka et al, 1996 ). Toluene, like other volatile organic compounds (VOCs), which include benzene, ethyl benzene, and xylene, in the process of biological treatment are partly biodegraded, or stripped to the atmosphere during aeration ( Zu et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations and measurements of VOCs, particularly BTEX compounds at several municipal wastewater treatment plants (WWTPs), have also shown relatively high concentrations of toluene in the anaerobic digested sludge supernatant. The concentrations of toluene varied over a wide range from 50 to 1760 μg/L ( Suschka et al, 1996 ). The concentration of benzene, ethylobenzene, and xylenes were detected at the lower range 0 to 152 μg/L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source of THMs was drinking water chlorinating and also usage of domestic disinfectants contribute to formation of THMs. Suschka et al [13] have Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors studied the occurrence of VOCs in sewage sludge [2,3], as well as in different parts of the WWTPs [4]: in the inlet wastewater, in water after some treatments and in the environmental air. These authors reported high concentrations of toluene and xylenes.…”
Section: Introductionmentioning
confidence: 99%